2020
DOI: 10.1186/s13567-020-00750-8
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the transmission dynamics of bovine digital dermatitis in New Zealand pastoral dairy production systems

Abstract: Bovine digital dermatitis (DD) is an important infectious cause of cattle lameness worldwide that has become increasingly prevalent in New Zealand pastoral dairy herds. In this study, a simplified DD scoring system after considering both M and Iowa DD scoring systems was applied to explore the transmission dynamics of DD in a typical springcalving pastoral New Zealand dairy herd. The modified model only included three compartments: normal skin, early stage lesions and advanced lesions. Lesions regressing after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…These figures are greatly lower than the reported DD prevalence in the present study. Pasture-based dairy herds have been frequently reported to be at lower risk of developing DD [ 38 ] which could explain the variation in the prevalence estimates. Studies performed on free-stall dairy herds reported much higher cow-level (20.5–66.4%), herd-level (96.1–97%) and within-herd (0–74.3%) prevalence of DD [ 39 41 ] than the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These figures are greatly lower than the reported DD prevalence in the present study. Pasture-based dairy herds have been frequently reported to be at lower risk of developing DD [ 38 ] which could explain the variation in the prevalence estimates. Studies performed on free-stall dairy herds reported much higher cow-level (20.5–66.4%), herd-level (96.1–97%) and within-herd (0–74.3%) prevalence of DD [ 39 41 ] than the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These gures are greatly lower than the reported DD prevalence in the present study. Pasture-based dairy herds have been frequently reported to be at lower risk of developing DD (42) which could explain the variation in the prevalence estimates. Studies performed on free-stall dairy herds reported much higher cow-level (20.5-66.4%), herd-level (96.1-97%) and within-herd (0-74.3%) prevalence of DD (43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…As podopatias são dinâmicas, evoluem ao longo do tempo, como comprovam estudos clínicos de tempo de recuperação com o tratamento e recorrência de animais afetados (Berry et al, 2012;Yang et al, 2020). A perícia veterinária deve considerar o tempo como uma variável nas avaliações do bemestar e suas relações com a dor e sofrimento de animais.…”
Section: Introductionunclassified